Methods for economic analysis of agroforestry systems: A review - Kareemulla, K. (Indian Journal of Agroforestry, 2020)
Agroforestry systems contribute rent, interest and wages, as they are a form of land use management that interacts with capital and labour. Presence of trees and woody perennials make economic analysis a little bit tricky, but with certain assumptions and scenarios, the same can be done. Besides the products and services, the agroforestry systems contribute to the livelihoods and natural resource management. Several economic tools such as cost benefit analysis, marketable surplus, demand and supply, price trends and modelling of farmer decisions etc. could be used to analyse the agroforestry systems. Besides a review, an introduction and brief illustration of some of these methods is dealt in this paper. The market dimensions of agroforestry products and services are also covered.